1985
DOI: 10.1111/j.1469-8137.1985.tb02825.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Population and Community Development in Cut Beech Logs

Abstract: SUMMARYThe spatial development, in beech logs exposed to air-borne and soil-borne inoculum, of mature fungal communities containing mutually or unilaterally exclusive mycelia of decay species is described and related to the ecological strategies and interaction of participant individuals. A combative heirarchy is recognized between (i) ruderal and/or stress-tolerant individuals which are spatially dominant early on and then decline, through (ii) air-borne combative individuals of decay fungi, such as Coriolus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
3

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 12 publications
6
68
3
Order By: Relevance
“…However, recent studies (Dickie et al 2012;Dowson et al 1988a, b;Fukami et al 2010;Fukasawa et al 2009) have demonstrated a high degree of interaction among co-existing fungal species, suggesting that WIF may invest more energy into competing with one-another than on producing wood-degrading enzymes under natural field conditions. Coates and Rayner (1985) also found that interaction reduced the rate of wood decay. Therefore, as demonstrated in this work, the high species richness of deadwood-resident fungal communities need not be associated with any increase in the production of wood degrading enzymes or wood decomposition rate.…”
Section: The Role Of Wif In Ecosystem Functions and Processesmentioning
confidence: 90%
“…However, recent studies (Dickie et al 2012;Dowson et al 1988a, b;Fukami et al 2010;Fukasawa et al 2009) have demonstrated a high degree of interaction among co-existing fungal species, suggesting that WIF may invest more energy into competing with one-another than on producing wood-degrading enzymes under natural field conditions. Coates and Rayner (1985) also found that interaction reduced the rate of wood decay. Therefore, as demonstrated in this work, the high species richness of deadwood-resident fungal communities need not be associated with any increase in the production of wood degrading enzymes or wood decomposition rate.…”
Section: The Role Of Wif In Ecosystem Functions and Processesmentioning
confidence: 90%
“…However, the extension rate of diffuse mycelium of cord-formers is slow, at least in culture, and the strategy of these fungi is apparently more concerned with establishment, via production of extensive superficial mycelium, of a sound base from which slow advancement into the main body of wood can occur, accompanied by replacement of fungi with inferior combative ability. This will be discussed further in our next, and final paper in this series, where we will consider the implication of differing ecological strategies and combative abilities for the spatial dynamics of the decay communities (Coates & Rayner, 1985b).…”
Section: Discussionmentioning
confidence: 99%
“…l(d)] or, eventually, of uniform white rot due to one or other of the cord formers (see Coates & Rayner, 1985b), emerged far more readily at the basal surface than near the aerial surface where discolouration persisted for a greater or lesser period before resolution into decay columns. Consistent with this, the occurrence of large numbers of individuals in small volumes of wood, observed near the aerial surface (Coates & Rayner, 1985a), was not detected by isolation studies from basal wood sections (Table 2).…”
Section: Numbers Of Genotypes Participating In Colonization Of the Bumentioning
confidence: 99%
“…As beautifully shown by Rayner, Boddy and their co-workers (Boddy & Rayner 1983c, Coates & Rayner 1985c, Rayner et al 1987, Chapela & Boddy 1988a, b, c, Rayner & Boddy 1988b, Griffith & Boddy 1990, Boddy 1993, wood-inhabiting fungi make up both temporally and spatially changing populations and communities, and the population and community structure and de elopment are based on dynamic interactions of species and individuals (genets). Although the basic biochemical and physiological pathways in wood decomposition, and the general patterns of mycelial dynamics in wood are fairly well known in vitro (Rayner & Boddy 1988a, Eriksson et al 1990, quantitative data on mycelial dynamics, populations and communities is available for just a few species of wood-inhabiting fungi, and most of it for managed forests of the temperate zone.…”
Section: Introductionmentioning
confidence: 99%